Prediction of effluent COD concentration of UASB reactor using kinetic models of monod, contois, second-order Grau and modified stover-kincannon - Seyyed Mehran Abtahi; Mohammad Mehdi Amin; Roya Nateghi; Ali Vosoogh; Mehdi Gholizadeh Dooranmahalleh (International Journal of Environmental Health Engineering, 2013)
Aims: The aim of this study is predicting the effluent COD of UASB reactors with flowing mathematical models. Materials and Methods: Weak industrial wastewater of the township, after passing screening unit, grit removal chamber and equalization tank, entered UASB reactor with volume of 144 m 3 (Length and width: 6 m; useful depth: 4 m). Analyses of laboratory parameters were done in accordance with water and wastewater standards. Results: The reactor start-up started with hydraulic retention time of 14.4 d and organic loading rate of 0.04 Kg COD/m 3 .d or 0.02 Kg BOD 5 /m 3 .d which in 200 days, hydraulic retention time reached to 0.9 d and organic loading rate reached to 0.85 Kg COD/m 3 .d or 0.45 Kg BOD 5 /m 3 .d eventually, that the highest COD and BOD 5 removal efficiencies were observed up to 70% and 64%, respectively in the hydraulic retention time of 0.9 d. In the kinetic evaluation, the equations for effluent COD concentration prediction were obtained after calculating kinetic coefficients of Y, K d , K, K S and μmax in the Monod model; β and μmax in the Contois model; α, β and K 2(S) in the second-order Grau model and K B and U max in the modified Stover-Kincannon model. Conclusion: The effluent COD concentration of reactor is a function of influent COD concentration of reactor in the modified Stover-Kincannon and second-order Grau models that have highest correlation coefficients while, it is a function of reactor′s solids retention time in Contois and Monod models.